Does corporate ownership structure affect its strategy towards diversification? - Amihud, Yakov; Lev, Baruch (Strategic Management Journal, 1999)
We claim that there is a link between corporate control structure and managers’ strategy towards unrelated mergers and risk diversification. Companies with greater ownership concentration are less diversified. Evidence also shows that corporate diversification generally results in value loss while focussing is value increasing. This highlights the potentially detrimental effect of agency problems on corporate strategy. Copyright © 1999 John Wiley & Sons, Ltd.